Na(+)-dependent Cl-HCO3 exchange in the squid axon. Dependence on extracellular pH (The Rockefeller University Press, 1992)
Intracellular pH (pHi) in squid giant axons recovers from acid loads by means of a Na(+)-dependent Cl-HCO3 exchanger, the actual mechanism of which might be exchange of: (i) external Na+ and HCO3- for internal Cl- and H+, (ii) Na+ plus two HCO3- for Cl-, (iii) Na+ and CO3= for Cl-, or (iv) the NaCO3- ion pair for Cl-. Here we examine sensitivity of transport to changes of extracellular pH (pHo) in the range 7.1-8.6. We altered pHo in four ways, using: (i) classical "metabolic" disturbances in which we varied [HCO3-]o, [NaCO3-]o, and [CO3=]o at a fixed [CO2]o; (ii) classical "respiratory" disturbances in which we varied [CO2]o, [NaCO3-]o, and [CO3=]o at a fixed [HCO3-]o; (iii) novel mixed-type acid- base disturbances in which we varied [HCO3-]o and [CO2]o at a fixed [CO3=]o and [NaCO3-]o; and (iv) a second series of novel mixed-type disturbances in which we varied [CO2]o, [CO3=]o, and [Na+]o at a fixed [HCO3-]o and [NaCO3-]o. Axons (initial pHi approximately 7.4) were internally dialyzed with a pH 6.5 solution containing 400 mM Cl- but no Na+. After pHi, measured with a glass microelectrode, had fallen to approximately 6.6, dialysis was halted. The equivalent acid extrusion rate (JH) was computed from the rate of pHi recovery (i.e., increase) in the presence of Na+ and HCO3-. When pHo was varied by method (i), which produced the greatest range of [CO3=]o and [NaCO3-]o values, JH increased with pHo in a sigmoidal fashion; the relation was fitted by a pH titration curve with a pK of approximately 7.7 and a Hill coefficient of approximately 3.0. With method (ii), which produced smaller changes in [CO3=]o and [NaCO3-]o, JH also increased with pHo, though less steeply. With method (iii), which involved changes in neither [CO3=]o nor [NaCO3-]o, JH was insensitive to pHo changes. Finally, with method (iv), which involved changes in neither [HCO3-] nor [NaCO3-]o, but reciprocal changes in [CO3=]o and [Na+]o, JH also was insensitive to pHo changes. We found that decreasing pHo from 8.6 to 7.1 caused the apparent Km for external HCO3- ([Na+]o = 425 mM) to increase from 1.0 to 26.7 mM, whereas Jmax was relatively stable. Decreasing pHo from 8.6 to 7.4 caused the apparent Km values for external Na+ ([HCO3-]o = 48 mM) to increase from 8.6 to 81 mM, whereas Jmax was relatively stable.(ABSTRACT TRUNCATED AT 400 WORDS)